FGF21 ameliorates diabetic nephropathy through CDK1-dependently regulating the cell cycle - Zhang, Yudie; Wang, Fan; Zhang, Chongyang; Yao, Fan; Zhang, Bin; Zhang, Yongping; Sun, Xiaobo (Frontiers in Pharmacology, 2025)
BackgroundDiabetic nephropathy (DN) is a prevalent global renal illness and one of the main causes of end-stage renal disease (ESRD). FGF21 has been shown to ameliorate diabetic nephropathy, and in addition FGF-21-treated mice impeded mitogenicity, whereas it is unclear whether FGF21 can influence DN progression by regulating the cell cycle in diabetic nephropathy.MethodsIn order to create a diabetic model, STZ injections were given to C57BL/6J mice for this investigation. Then, FGF21 was administered, and renal tissue examination and pathological observation were combined with an assessment of glomerular injury, inflammation, oxidative stress, and the fibrinogen system in mice following the administration of the intervention. Furthermore, we used db/db mice and FGF21 direct therapy for 8 weeks to investigate changes in fasting glucose and creatinine expression as well as pathological changes in glomeruli glycogen deposition, fibrosis, and nephrin expression. To investigate the mechanism of action of FGF21 in the treatment of glycolytic kidney, transcriptome sequencing of renal tissues and KEGG pathway enrichment analysis of differential genes were performed.ResultsThe study’s findings demonstrated that FGF21 intervention increased clotting time, decreased oxidative stress and inflammation, and avoided thrombosis in addition to considerably improving glomerular filtration damage. After 8 weeks of FGF21 treatment, glomerular glycogen deposition, fibrosis, and renin expression decreased in db/db mice. Moreover, there was a notable reduction of creatinine and fasting blood glucose levels. Additionally, the CDK1 gene, a key player in controlling the cell cycle, was discovered through examination of the transcriptome sequencing data. It was also shown that FGF21 dramatically reduces the expression of CDK1, which may help diabetic nephropathy by averting mitotic catastrophe and changing the renal cell cycle.ConclusionIn short, FGF21 improved the development of diabetic nephropathy in diabetic nephropathy-affected animals by reducing glomerular filtration damage, inflammation, and oxidative stress, inhibiting the formation of thrombus, and controlling the cell cycle through CDK1.